Challenges and insights from holistic sustainability reporting for shrimp fisheries in different jurisdictions. (12th July 2020) - Hornborg, Sara; Hobday, Alistair J; Ogier, Emily; Fleming, Aysha; Thomas, Linda; Hartog, Jason R
Abstract: Sustainability of fisheries extends beyond environmental aspects. Broad information is today sought for decision-making and by many stakeholders. Here, a framework recently developed to comprehensively report on sustainability issues relevant to fisheries, the Australian Fisheries Healthcheck, was used to compare five crustacean trawl fisheries from Australia and Europe. Indicators covered 51 different aspects of sustainability in 24 sub-categories related to ecological, economic, social and ethical, governance, and external (e.g. climate, contaminants) dimensions. We found that data availability did not vary greatly between fisheries, but the indicator outcomes did. Furthermore, while environmental sustainability has received most attention in assessments to date, the associated indicators had the least publicly available data. Another finding was that eco-certification and high performance on several governance indicators did not necessarily equate to sustainability. For future international comparisons, challenges include identifying comparable and cost-effective metrics for indicators derived from different data collection strategies. Commencing holistic reporting on broader sustainability is important since the data provided (i) are sought by stakeholders; (ii) enable improved availability of empirical data for research on the effectiveness of different governance modes; (iii) can illustrate trade-offs between different dimensions of sustainability, and (iv) build trust in the fishery system as producers of sustainable food.